Efeito da promoção de turbulência na hidrodinâmica de um reator tipo filtro-prensa e na degradação eletroquímica do bisfenol S - Wachter, Naihara (Universidade Federal de São Carlos, 2019)
The kinetics of many electrochemical processes is limited by mass transport, especially at low concentrations of the reactant. The use of turbulence promoters in parallel-plate reactors increases the hydrodynamic turbulence of the solution and consequently causes a reduction of the thickness of the diffusion layer and an increase of the rate of delivery of reactants to the electrode surface. In this sense, the objective of this work was to study the effect of turbulence promotion on the hydrodynamics of a filter-press reactor fitted with a boron-doped diamond anode (Si/BDD, [B]/[C] = 500 ppm) and on the electrochemical degradation/mineralization of bisphenol S. The results of the hydrodynamic characterizations of the electrochemical reactor show that the use of a turbulence promoter of three stacked meshes causes approximately a threefold increase of the mass transfer coefficient (from 3.25 x 10–5 to 9.44 x 10–5 m s–1) and of the limiting current density for the electro-oxidation of bisphenol S (from 6.88 to 20.0 mA cm–2), at a flow rate (qV) of 7.0 L min–1 and 25 °C. Afterwards, the effects of the quantities pH, flow rate and current density on the electrochemical degradation and mineralization of bisphenol S (100 mg L–1 solution in 0.1 mol L–1 Na2SO4) were investigated in the absence and presence of the turbulence promoter. Under the optimized electrolysis conditions (uncontrolled pH, qV = 7.0 L min–1, j = 14 mA cm–2, and 25 °C), 80% removal of the total organic carbon (TOC) was obtained after 283 or 450 min, for electrolyses performed in the presence or absence of the turbulence promoter, respectively. For this extent of TOC removal, the energy consumption was about 0.43 or 0.28 kW h g–1 (of TOC), in the absence or presence of the turbulence promoter, respectively; thus, the use of the turbulence promoter caused a reduction of about 35% in energy consumption. Under this optimized condition, six initial degradation intermediates were identified, regardless of the hydrodynamic condition used, but in the condition of higher turbulence these intermediates were formed and totally consumed within a shorter electrolysis time. Hence, it can be concluded that the use of the turbulence promoter of three stacked meshes leads to an enhancement of the bisphenol S degradation/mineralization kinetics, but does not affect its reaction mechanism.
The effect of turbulence promotion on the hydrodynamics of a filter-press reactor and on the electrochemical degradation of bisphenol S
Keywords: Degradação eletroquímica; Diamante dopado com boro; Bisfenol S; Promotor de turbulência; Transporte de massa; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA